Risk Management of Wastewater Treatment in the Wastewater Treatment Plant of PT. X - Fauziah Raya Shinta; Nieke Karnaningroem; Mas Agus Mardyanto (Institut Teknologi Sepuluh Nopember, 2019)
The economic rise as much as 5.5% in East Java region in the first quarter of 2018 compared to the first quarter of 2017, was due to the main supporting factor of an increase in the number of industries. An increase in industry has the potential to cause environmental pollution, especially in water bodies as evidenced by an index of water quality conditions for East Java rivers that now stands on Class II. Currently, PT. X in East Java is working on the expansion of its company. This study aims to identify the risks of wastewater treatment of PT. X using the fishbone analysis method and determine the priority of failures that must be handled using the FMEA method.For research purposes, two types of data are used, namely secondary and primary data. Secondary data includes flow chart of wastewater treatment, wastewater quality report and standard operating procedures. Meanwhile, the primary data for the quality of wastewater treatment was obtained through sampling, which was carried out at each wastewater treatment unit as well as the results of questionnaire with direct interviews. From those two types of data, an analysis of the potential occurrence of risk arises by using a fishbone analysis diagram. The risk results obtained through fishbone analysis are then processed using the Failure Mode and Effects Analysis (FMEA) method to obtain a Risk Priority Number (RPN). Then, the results of risk analysis from fishbone analysis are assessed into a priority of failures, expressed in Risk Priority Number (RPN).Based on the analysis of research data, it was concluded that the problem that occurred in wastewater treatment was inefficient wastewater treatment. The inefficient process was caused by the WWTP design conditions that were greater than the inlet discharge. Based on the results of data processing using the FMEA method, it was found that the largest RPN value was 125